2007
DOI: 10.1029/2006gl028190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tidal stresses on volcanic activity at Mount Etna, Italy

Abstract: Here we model quantitatively the stress and strain induced by tidal forces as possible triggers of Mount Etna eruptions during 1989, 2000 and 2001, by means of 2D numerical analysis by finite difference method applied to the volcano edifice. Spectral and vectorial analysis of tidal acceleration indicates that the quasi‐diurnal, semi‐diurnal and ter‐diurnal constituents may have induced decompressions up to some kPa in the shallow (i.e., 1,500 m) gas‐saturated magma reservoir, which controlled magma vesiculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 36 publications
(56 reference statements)
3
42
0
1
Order By: Relevance
“…Previous works (Bozzano et al, 2013;Sottili et al, 2007) brought evidences that, on hourly to daily timescales, the periodic decompression induced by tidal stresses on Mount Etna shallow plumbing system may act as a trigger mechanism for eruptive activity on condition that the eruptive system is already close to a critical state. At Mount Etna, this mechanism of tidal triggering of lava fountaining episodes is statistically more evident when the horizontal component of the quasi-diurnal tidal stresses acts in parallel with the ongoing eastern volcano flank instability (Sottili et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous works (Bozzano et al, 2013;Sottili et al, 2007) brought evidences that, on hourly to daily timescales, the periodic decompression induced by tidal stresses on Mount Etna shallow plumbing system may act as a trigger mechanism for eruptive activity on condition that the eruptive system is already close to a critical state. At Mount Etna, this mechanism of tidal triggering of lava fountaining episodes is statistically more evident when the horizontal component of the quasi-diurnal tidal stresses acts in parallel with the ongoing eastern volcano flank instability (Sottili et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Through a simple time-predictable model, and by assuming a constant magma supply rate, it has been proposed that eruptions occur when the amount of stored magma reaches a critical value (Hill et al, 1998). Under these conditions, when the Mount Etna plumbing system is close to a critical state, the effects of decompression induced by external actions, as tidal forces (Sottili et al, 2007) and earthquakes (Bozzano et al, 2013) seem to affect the timing of eruptions at Mount Etna on short (days to hours) timescales. In our analysis, we considered the starting date and the magnitude of eruptions defined here as the logarithm of the erupted mass (in kg) of magma (e.g., Pyle, 2000).…”
Section: Eruptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…corresponding to ±45 Pa/h for typical annual ΔLOD values). For comparison, decompression rates related to glacio-eustatism and tidal forces, considered among possible controlling factors of volcanic eruptions, range in the order of a few Pa per year (Kutterolf, et al 2012) and 150 Pa/h (Sottili et al 2007), respectively, whilst magma volatile pressure build-up is reported around 400-720 Pa/h (Johnston and Mauk 1972;Jentzsch et al 2001). …”
Section: Influence Of Lod Changes On Subduction Volcanoesmentioning
confidence: 99%
“…due to global tectonism, glacio-eustatism and tidal forces; Kutterolf et al 2012;Sottili et al 2007). The recently described causal relationship between LOD changes and volcanic eruptions (Palladino and Sottili 2014) provides the background to understand how yearly LOD changes perturb the state of stress in specific geodynamic contexts.…”
Section: Introductionmentioning
confidence: 99%